THE INFLUENCE OF INTERNAL CONTROL SYSTEM ON THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AT DR. WAHIDIN SUDIROHUSODO HOSPITAL IN MAKASSAR - Anugerah Satria Putra; Haliah; Andi Kusumawati (ZILLZELL MEDIA PRIMA, 2023)
This research aims to examine and analyze the influence of the internal control system and organizational culture on the implementation of good corporate governance. Data analysis was carried out using primary data on questionnaire answers from hospital employees and then analyzed quantitatively, namely regression analysis using SPSS. The results of this research show that the internal control system has a positive and significant effect on good corporate governance. This shows that a good internal control system can improve the implementation of good corporate governance.